Santri’s Community in Political Change: Historical Interpretive - Aminuddin, M Faishal (Islamic Insights Journal, 2019)
This study seeks to understanding the historical context of the construction and position of of Santri’s community in Javanese society. Evidences from case study in an agrarian village in East Java proved that political change had potentially eroded the patrimonial system which embedded in this community. The analysis drawn from research findings which scattering the complexity of indigenous factors covering historical background, institutional change, cultural form and economical mode of production within society. Using morphogenetics approach coupled with ethnographical methods, this research found that patrimonial system in santri’s community as traditional Islam backbone has shifted. From being a closed patron-cliental relationship, now it becomes more open and diverse. This study contributes to explain political legitimacy in Islamic-based organization in Indonesian politics after the authoritarian New Order regime. Particularly to capture what happens in the micro-level political phenomenon. This study also reveals the neglected and critical phase in Indonesia democratic transition from below.